Determination of phytoplankton composition by microscopy and HPLC-derived pigment analysis in the Sea of Marmara - DURSUN, FUAT; TAS, SEYFETTİN and BAYRAM PARTAL, FATMA and EDİGER, DİLEK (Mediterranean Marine Science, 2020)
This study is an integrated overview of pigment and microscopic analysis of phytoplankton composition in the Sea of Marmara. The study was conducted from 27 sampling stations during spring (May 2017 and 2018) and summer (August 2016 and 2018). The phytoplankton community was represented mostly by diatoms and dinoflagellates, as the major groups, and also other phytoflagellate groups as shown by both techniques. Chlorophyll-a, chlorophyll-c1+c2, peridinin, 19’-butanoyloxyfucoxanthin, fucoxanthin, zeaxanthin, alloxanthin, 19’-hexanoyloxyfucoxanthin, diadinoxanthin, chlorophyll-b and ß-carotene concentratios were determined by High Performance Liquid Chromatography (HPLC). A total of 124 eukaryotic taxa belonging to eight algal classes were found through microscopic analysis. 60 taxa of them were dinoflagellates, 52 taxa were diatoms and 12 taxa were other phytoflagellates. The number of diatoms and dinoflagellates, as the major groups, accounted for 90.4% of the total phytoplankton species. Chlorophyll-a, fucoxanthin and peridinin concentrations varied between 0.03-7.20, 0.01-5.23 and 0.01-2.14 μg L-1, throughout the research period, respectively. The highest chlorophyll-a values were measured at stations MD26 (7.20 µg L-1) and MD22 (6.61 µg L-1) in May 2018, which were located at Gemlik and Bandirma bays. There was a significant correlation (r:0.87, p<0.001 n:54) between HPLC determined fucoxanthin concentrations and diatom abundances in August 2016 and 2018. Also, higher chlorophyll-c1+c2 concentrations revealed consistency with high diatom abundances and fucoxanthin concentrations in August 2016 and 2018. This result confirmed that diatoms are the most important carrier of fucoxanthin and it can be used for taxonomic evaluation of diatom community of the Sea of Marmara.